ASSOCIATION BETWEEN PHYSICAL ACTIVITY AND VITAMIN D ACCORDING TO BMI LEVEL AMONG ICELANDIC OLDER ADULTS. (11th November 2018) - Chang Gudjonsson, M; Geirsdottir, O; Jonsson, P; Thorsdottir, I; Ramel, A
Abstract: Background: The association between obesity and vitamin D level has been reported in community-dwelling healthy adults as well as in hospitalized patients. A deficit of 25 hydroxyvitamin D (25OHD) is also associated with various negative health consequences in older adults. The aim of the current study was to compare 25OHD in different BMI status (obese, normal, overweight) with particular consideration of physical activity, season and fish oil intake, the most important dietary source of vitamin D in Iceland. Methods: Total of 236 Subjects (73.7 ± 5.7 years) participated in the cross-sectional study. Anthropometrics, health screening questionnaire, physical & cognitive function, physical activity, dietary intake, parathyroid hormone, and quality of life (QoL) were measured. Results: Mean concentrations of 25OHD were 66.7 ± 28.1 nmol/L in our participants. Obese participants had lower 25OHD, higher parathyroid hormone, exercised less and were less likely to take fish oil compared with normal and overweight participants. The results indicate that physical activity was associated with higher 25OHD among people with normal- and overweight BMI but not in people with obese BMI. Fish oil intake was associated with higher 25OHD independently from BMI status. Conclusions: Our study shows that obese community-dwelling older adults in Iceland have lower 25OHD than their normal-/overweight counterparts. We also found that the level of leisure time physical activity was associated with higher 25OHD in normal-/overweight, but not in obese participants. On the other hand, vitamin D supplementation in the form of fish oil was associated with higher 25OHD regardless of BMI status.